Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To determine which pair of expressions represents inverse functions, we need to verify that for a given pair of functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex], the following conditions are met:
1. [tex]\( f(g(x)) = x \)[/tex]
2. [tex]\( g(f(x)) = x \)[/tex]
Let's analyze each option step-by-step:
Option A:
[tex]\[ f(x) = \frac{4 - 3x}{4x - 2}, \quad g(x) = \frac{x + 2}{x - 2} \][/tex]
1. [tex]\( f(g(x)) = f\left(\frac{x + 2}{x - 2}\right) \)[/tex]:
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f\left(\frac{x + 2}{x - 2}\right) = \frac{4 - 3\left(\frac{x + 2}{x - 2}\right)}{4\left(\frac{x + 2}{x - 2}\right) - 2} \][/tex]
2. [tex]\( g(f(x)) = g\left(\frac{4 - 3x}{4x - 2}\right) \)[/tex]:
Substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex]:
[tex]\[ g\left(\frac{4 - 3x}{4x - 2}\right) = \frac{\left(\frac{4 - 3x}{4x - 2}\right) + 2}{\left(\frac{4 - 3x}{4x - 2}\right) - 2} \][/tex]
After simplifying, we find that [tex]\( f(g(x)) \neq x \)[/tex] and [tex]\( g(f(x)) \neq x \)[/tex]. Therefore, these functions are not inverses.
Option B:
[tex]\[ f(x) = \frac{x + 3}{4x - 2}, \quad g(x) = \frac{2x + 3}{4x - 1} \][/tex]
1. [tex]\( f(g(x)) = f\left(\frac{2x + 3}{4x - 1}\right) \)[/tex]:
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f\left(\frac{2x + 3}{4x - 1}\right) = \frac{\frac{2x + 3}{4x - 1} + 3}{4\left(\frac{2x + 3}{4x - 1}\right) - 2} = x \][/tex]
2. [tex]\( g(f(x)) = g\left(\frac{x + 3}{4x - 2}\right) \)[/tex]:
Substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex]:
[tex]\[ g\left(\frac{x + 3}{4x - 2}\right) = \frac{2\left(\frac{x + 3}{4x - 2}\right) + 3}{4\left(\frac{x + 3}{4x - 2}\right) - 1} = x \][/tex]
These simplifications confirm that [tex]\( f(g(x)) = x \)[/tex] and [tex]\( g(f(x)) = x \)[/tex]. Therefore, [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] are indeed inverse functions.
Option C:
[tex]\[ f(x) = \frac{4x + 2}{x - 3}, \quad g(x) = \frac{5x + 3}{4x - 2} \][/tex]
1. [tex]\( f(g(x)) = f\left(\frac{5x + 3}{4x - 2}\right) \)[/tex]:
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f\left(\frac{5x + 3}{4x - 2}\right) = \frac{4\left(\frac{5x + 3}{4x - 2}\right) + 2}{\left(\frac{5x + 3}{4x - 2}\right) - 3} \][/tex]
2. [tex]\( g(f(x)) = g\left(\frac{4x + 2}{x - 3}\right) \)[/tex]:
Substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex]:
[tex]\[ g\left(\frac{4x + 2}{x - 3}\right) = \frac{5\left(\frac{4x + 2}{x - 3}\right) + 3}{4\left(\frac{4x + 2}{x - 3}\right) - 2} \][/tex]
After simplification, it is concluded that these expressions do not satisfy the inverse conditions.
Option D:
[tex]\[ f(x) = 2x + 5, \quad g(x) = 2 + 5x \][/tex]
1. [tex]\( f(g(x)) = f(2 + 5x) \)[/tex]:
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(2 + 5x) = 2(2 + 5x) + 5 = 4 + 10x + 5 = 9 + 10x \neq x \][/tex]
2. [tex]\( g(f(x)) = g(2x + 5) \)[/tex]:
Substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex]:
[tex]\[ g(2x + 5) = 2 + 5(2x + 5) = 2 + 10x + 25 = 27 + 10x \neq x \][/tex]
Therefore, these functions are also not inverses.
After reviewing all options:
The pair of expressions that represents inverse functions are those in Option B:
[tex]\[ \boxed{2} \][/tex]
1. [tex]\( f(g(x)) = x \)[/tex]
2. [tex]\( g(f(x)) = x \)[/tex]
Let's analyze each option step-by-step:
Option A:
[tex]\[ f(x) = \frac{4 - 3x}{4x - 2}, \quad g(x) = \frac{x + 2}{x - 2} \][/tex]
1. [tex]\( f(g(x)) = f\left(\frac{x + 2}{x - 2}\right) \)[/tex]:
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f\left(\frac{x + 2}{x - 2}\right) = \frac{4 - 3\left(\frac{x + 2}{x - 2}\right)}{4\left(\frac{x + 2}{x - 2}\right) - 2} \][/tex]
2. [tex]\( g(f(x)) = g\left(\frac{4 - 3x}{4x - 2}\right) \)[/tex]:
Substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex]:
[tex]\[ g\left(\frac{4 - 3x}{4x - 2}\right) = \frac{\left(\frac{4 - 3x}{4x - 2}\right) + 2}{\left(\frac{4 - 3x}{4x - 2}\right) - 2} \][/tex]
After simplifying, we find that [tex]\( f(g(x)) \neq x \)[/tex] and [tex]\( g(f(x)) \neq x \)[/tex]. Therefore, these functions are not inverses.
Option B:
[tex]\[ f(x) = \frac{x + 3}{4x - 2}, \quad g(x) = \frac{2x + 3}{4x - 1} \][/tex]
1. [tex]\( f(g(x)) = f\left(\frac{2x + 3}{4x - 1}\right) \)[/tex]:
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f\left(\frac{2x + 3}{4x - 1}\right) = \frac{\frac{2x + 3}{4x - 1} + 3}{4\left(\frac{2x + 3}{4x - 1}\right) - 2} = x \][/tex]
2. [tex]\( g(f(x)) = g\left(\frac{x + 3}{4x - 2}\right) \)[/tex]:
Substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex]:
[tex]\[ g\left(\frac{x + 3}{4x - 2}\right) = \frac{2\left(\frac{x + 3}{4x - 2}\right) + 3}{4\left(\frac{x + 3}{4x - 2}\right) - 1} = x \][/tex]
These simplifications confirm that [tex]\( f(g(x)) = x \)[/tex] and [tex]\( g(f(x)) = x \)[/tex]. Therefore, [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] are indeed inverse functions.
Option C:
[tex]\[ f(x) = \frac{4x + 2}{x - 3}, \quad g(x) = \frac{5x + 3}{4x - 2} \][/tex]
1. [tex]\( f(g(x)) = f\left(\frac{5x + 3}{4x - 2}\right) \)[/tex]:
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f\left(\frac{5x + 3}{4x - 2}\right) = \frac{4\left(\frac{5x + 3}{4x - 2}\right) + 2}{\left(\frac{5x + 3}{4x - 2}\right) - 3} \][/tex]
2. [tex]\( g(f(x)) = g\left(\frac{4x + 2}{x - 3}\right) \)[/tex]:
Substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex]:
[tex]\[ g\left(\frac{4x + 2}{x - 3}\right) = \frac{5\left(\frac{4x + 2}{x - 3}\right) + 3}{4\left(\frac{4x + 2}{x - 3}\right) - 2} \][/tex]
After simplification, it is concluded that these expressions do not satisfy the inverse conditions.
Option D:
[tex]\[ f(x) = 2x + 5, \quad g(x) = 2 + 5x \][/tex]
1. [tex]\( f(g(x)) = f(2 + 5x) \)[/tex]:
Substitute [tex]\( g(x) \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(2 + 5x) = 2(2 + 5x) + 5 = 4 + 10x + 5 = 9 + 10x \neq x \][/tex]
2. [tex]\( g(f(x)) = g(2x + 5) \)[/tex]:
Substitute [tex]\( f(x) \)[/tex] into [tex]\( g(x) \)[/tex]:
[tex]\[ g(2x + 5) = 2 + 5(2x + 5) = 2 + 10x + 25 = 27 + 10x \neq x \][/tex]
Therefore, these functions are also not inverses.
After reviewing all options:
The pair of expressions that represents inverse functions are those in Option B:
[tex]\[ \boxed{2} \][/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.